A Practical Approach of Data Visualization from Geographic Information Systems by Using Mobile Technologies - Vasilev, Julian; Petrov, Pavel; Jordanov, Jordan (International Journal of Interactive Mobile Technologies (iJIM), 2024)
The purpose of this paper is to demonstrate a practical approach to data visualization by using mobile technologies and desktop geographic information systems. To do that, we analyze public data for Black Sea water pollution on Varna’s beaches by using real data in real time. Geographic information systems (GISs) are used for visualization, and statistical software is used for correlation analysis. In our approach, the use of open-source software products is essential, namely QGIS and PSPP software. The methodology includes using one dataset, and after extract-transform-load procedures, additional analysis is conducted. Mobile technologies are used to demonstrate the results of the correlation analysis to a wide audience, and data visualization helps for better understanding. A similar visualization approach may be conducted for other subjects and fields of interest.